Employer satisfaction with the competencies of a nursing graduate from a licensed public university - Huyhua Gutierrez, Sonia Celedonia (2020)
Objective: To evaluate the employer's satisfaction with the competences of the nursing graduate from the Toribio Rodríguez de Mendoza National University in Amazonas. Method: The study was of a quantitative approach, descriptive, prospective, cross-sectional level, having as a sample 74 employers; The method was hypothetical - deductive, survey technique and the instrument the questionnaire whose validity was carried out through expert judgment obtaining 8.881784 (adequate) and reliability through Crombach's alpha obtaining 0.954 (strong reliability), it was applied through the form of Google. Main results: 59.5% of the employers are moderately satisfied, 32.4% are satisfied and 8.1% are dissatisfied; Likewise, in the dimensions of social responsibility, research, assistance and management, employers are moderately satisfied (58.1%, 63.5%, 52.7% and 55.4%, respectively). General conclusion: The highest percentage of employers are moderately satisfied, based on this, five educational objectives are proposed to be included in the training curriculum by competencies and that allow clarifying goals of continuous improvement of Higher Education in Nursing. Descriptors (indicating unique identifier): satisfaction, employer, competence, graduate, nursing.